Lanthanum hydroxide protects kidney through gut microbiota in a rat model of chronic kidney disease - Yuan Gao; Shengnan Wang; Lijun Sun; Bing Li; Hong Liu; Ren Bu; Changhai Su; Min Guo; Yang Liu; Lulu Zhao; Chao Gu; Xiaojia Li; et al. (Wiley, 2024)
Abstract The progression of chronic kidney diseases (CKD) is complex, influenced by a myriad of factors including gut microbiota. While emerging evidence suggests that gut microbiota can have beneficial effects in managing CKD, it is also recognized that dysbiosis may contribute to the progression of CKD and associated uremic complications. Our previous research has demonstrated the efficacy of lanthanum hydroxide in delaying kidney failure and preserving renal function. However, the role of lanthanum hydroxide in modulating gut microbiota in this context remains unclear. In our study, we induced CKD in rats using adenine, leading to gut microbial dysbiosis, kidney pathology, and disturbances in amino acid metabolism. In this adenine‐induced CKD model with hyperphosphatemia, treatment with lanthanum hydroxide improved renal function. This improvement was associated with the restoration of gut microbial balance and an increase in urine ammonium metabolism. These results suggest that the therapeutic potential of lanthanum hydroxide in CKD may be partly due to its ability to reshape gut microbiota composition. This study underscores the significance of lanthanum hydroxide in kidney protection, attributing its benefits to the modulation of gut microbiota in a rat model of CKD.